AMPHIBIOLOGICAL NOTES III ON SOME ANURANS FROM THE STATE OF NUEVO LEON - MALDONADO KOERDELL, MANUEL (Hospital Spanish, CD MEXICO, DF, MEX, 1950)
A list of invalid names applied to spp of Aedes of the New World is accompanied by a statement of the valid name to which each is referable The paper complements a list of the spp of the same genus already published
REV SOC MEX HIST NAT
Keywords: AMPHIBIOLOGICAL NOTES III, ANURANS, NUEVO LEON; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); HERPETOLOGIA